Factors that cause endodontic failures in general practices in Japan - Mikiyo Yamaguchi; Yuichiro Noiri; Yoshihiro Itoh; Shungo Komichi; Kyoko Yagi; Reo Uemura; Haruna Naruse; Saori Matsui; Nanako Kuriki; Mikako Hayashi; Shigeyuki Ebisu (BMC, 2018)
Abstract Background Bacterial biofilms that develop on root surfaces outside apical foramens have been found to be associated with refractory periapical periodontitis. However, several other factors cause endodontic failures apart from extraradicular biofilms. The aim of this study was to identify the factors causing endodontic failures in general practices in Japan. Methods Patients diagnosed as having refractory periapical periodontitis by general practitioners and who requested endodontic treatment at Osaka University Dental Hospital were selected by checking medical records from April 2009 to March 2013. Factors causing endodontic failures were identified. Results A total of 103 teeth were selected, and 76 teeth completed root-canal treatment. Tooth extractions were required for 18 teeth after or without endodontic treatment. Six teeth required apicoectomy after endodontic treatment. One tooth needed hemisection. One tooth needed intentional replantation. One tooth needed adhesion and replantation. The main causes of treatment failure were open apices (24 teeth), perforation (18 teeth), and root fracture (13 teeth). In six teeth with open apices that required apicoectomy or extraction, extraradicular biofilms may have been related to endodontic failure. Conclusions Most endodontic cases diagnosed with refractory periapical periodontitis by general practitioners were compromised by any other factors rather than extraradicular biofilms.